Local Government and Network Governance in the Era of UN Sustainable Development Goals (SDGS): Gyeongsangbukdo Province and Daegu Metropolitan City in South Korea - Lim, Sojin; Jung, Sang-Hee (México y la Cuenca del Pacífico, 2020)
This article aims to discuss the roles of local governments in the era of Sustainable Development Goals (SDGs), with a case study of Gyeongsangbukdo Province and Daegu Metropolitan City in South Korea. The study looks at the main official development assistance (ODA) policies and activities of these two local governments, and how these two local governments have adopted the SDGs framework. In doing so, this study has employed the approach of network governance regarding the establishment of partnerships between a central authority and local governments and between local governments and other aid stakeholders at the local level. The findings of the study suggest that local governments’ ODA policies and activities in South Korea are barely commensurate with recent norm change at the international level. Given this, this study argues that local governments in South Korea need to develop their ODA capacity building in order to be in line with international norms.